U Uji Aktivitas Antibakteri Jamur Endofit Batang Bajakah Tampala (Spatholobus Littoralis Hassk) Pada Bakteri Salmonella Typhi - Elysa, Elysa; Chandra, M. Andi; Nastiti, Kunti (LPPM Universitas Sari Mulia, 2025)
Bajakah Tampala is often used by the people of Halong District Village for wisa disease or high fever which is believed to be typoid by boiling the bark of Bajakah Tampala (Spatholobus littoralis Hassk) wood. The use of traditional medicine from plants that are abundant in nature. This endophyte is research in the field of biotechnology using small samples from the original plant to obtain the same compounds as the original plant so that biodiversity is maintained. The aim of this research is to determine the type of endophytic fungi produced by Bajakah Tampala stem (Spatholobus Littoralis Hassk) and the greatest antibacterial activity of the endophytic fungi produced by Bajakah Tampala stem (Spatholobus Littoralis Hassk) using the diffusion method and to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against Salmonella typhi bacteria, the research method stage involves growing endophytic fungi, isolated and separated according to the type of fungus, followed by testing on Salmonella typhi bacteria. The greatest antibacterial activity was then determined by MIC and MBC by making various concentrations, and the positive control was chloramphenicol. The research found three types of endophyte isolates, Bajakah Endophyte Isolate 1 (IEB1), Bajakah Endophyte Isolate 2 (IEB2), Bajakah Endophyte Isolate 3 (IEB3), the results showed the largest potential inhibition zone in the IEB3 isolate was 28.78 mm compared to the antibiotic chloramphenicol with an inhibition zone of 24.42 mm. MIC testing shows the level of turbidity at a concentration of 6.25% and has a MBC that counts the number of colonies at a concentration of 25%. the result of the endophytic fungus Bajakah Tampala stem Spatholobus Littoralis Hassk) which has antibacterial activity and the ability to kill Salmonella typh bacteria